THE NEXUS OF ‘COOL’ MOTIVATION AND CREDIT CARD ON IMPULSE BUYING BEHAVIOR: A CONCEPTUAL STUDY (International Journal of Islamic Business, 2017)
The issue of impulse buying behavior has been studied in numerousmarketing fields particularly in buying behavior. Impulse buying behaviorhas been considered as one type of buying behavior frequently exercisedamong consumers in this modern age. There is a growing stream ofresearch on impulse buying behavior, particularly from the retailpurchasing context which revealed factors that contribute to thisbehavior. Generally, previous studies on impulse buying focused on threeperspectives, namely individual factors (e.g. lack of self-control), productfactors (e.g. low and high price), and situational factors (e.g. storeenvironment). However, there are scarce conceptual and theoreticalknowledge in marketing studies which discusses the influence of ‘cool’motivation and credit card on impulse buying behavior. Therefore, thepurpose of this conceptual paper is to review the relationship between‘cool’ motivation and credit card on impulse buying behavior which inturn is expected to reveal a new perspective on the study of consumerbehavior. It is essential to explore the relationship between ‘cool’motivation (CM), credit card (CC) and impulse buying behavior (IBB) asless attention has been paid to this matter. Therefore, the results of thisstudy will contribute to the current body of knowledge and provideadditional valuable information to marketing practitioners which thenwill allow them to create effective and efficient marketing strategies.